The plights of Eritrean refugees in the Shimelba Refugee Camp, Ethiopia. Issue 1 (6th March 2017) - Arega, Natnael Terefe
Abstract : Purpose: Thousands of Eritrean youth flee due to extreme domestic discontent with Eritrean Government. Little research has been done on Eritrean refugees in Ethiopia. The purpose of this paper is to explore the difficulties facing Eritrean refugees in the Shimelba Refugee Camp in northern Ethiopia. The study explores the refugees' pre-migration experiences as well as their life difficulties in the refugee camp. Design/methodology/approach: This study employed a cross-sectional qualitative approach. Relevant data were collected through personal interviews with a sample of 15 refugees. The study was also supplemented by the researcher's personal observations regarding the living conditions of the refugees in the camp. Findings: Gross human rights violations at home forced the Eritreans to flee in to Ethiopia. Refugees reported their experiences of arrest, torture, and abuse, due to their dissenting political and religious opinions. Moreover, they fled Eritrea to escape harsh compulsory conscription into the Eritrean military service. Unemployment and lack of income were also important push factors. Factors identified as threats to the psychosocial health of refugees at the refugee camp include the feeling of isolation, the absolute uncertainty of the future, fears concerning the safety of the family left behind, the strictness of the structure within the camp, and the fear of health-related problems associated with the limited health care facilities. Research limitations/implications: Further research investigating the mental health problems of the refugees employing quantitative methods is needed. Also, research about the potential avenues for ameliorating the challenges faced by these refugees is desirable. Originality/value: This paper gives an insight to the situation of Eritrean refugees in Ethiopia, which includes the reasons why they flee Eritrea, their experiences during flight, and the conditions in which Eritrean refugees live in the camp from the point of view of the refugees themselves. Understanding the challenges facing the refugees has implications for how short- and long-term policies can be altered to better serve them.